Tracking Eastward Displacement of Pacific Saury Fishing Grounds Using Nighttime Fishing Radiance: The Role of Early‐Season Kuroshio Extension Variability - Hao Tian; Hiroto Abe; Yang Liu; Bingqing Chen; Bin Kang; Jianchao Li; Sei‐Ichi Saitoh; Chang Cao; Wenjia Li; Hui Xu; Shuyang Ma; Yongjun Tian (Fisheries Oceanography, 2026)
Pacific saury ( Cololabis saira ) is an ecologically and commercially important small pelagic species in the northwestern Pacific, where fishing grounds have shifted markedly eastward in recent years. However, the role of early‐season oceanographic variability in shaping this redistribution remains poorly understood. Using catch records, Automatic identification systems‐derived fishing hours, vessel registry data, and nighttime light (NTL) observations, we examined fishing activity during 2012–2020 and linked fishing‐ground displacement to environmental variability and Kuroshio Extension system (KES) hydrographic conditions. NTL radiance outperformed CPUE and fishing hours in representing environmentally structured fishing‐ground variability, highlighting its value for tracking transboundary displacement in this light‐luring fishery. The optimal random forest model identified mixed layer depth, sea surface salinity, phytoplankton carbon, and sea surface temperature (SST) as the dominant predictors. Radiance‐weighted centers of gravity revealed especially strong eastward displacement in 2019–2020. Early‐season (May–July) displacement was strongly associated with annual displacement, indicating that the annual fishing‐ground pattern was largely preconditioned during the early‐season. Among the dominant environmental variables, SST displacement in the traditional fishing grounds showed the strongest relationship with the eastward shift. Years with longer Kuroshio Extension fronts and higher regional mean KE showed greater eastward displacement, indicating an association between early‐season KES‐related hydrographic variability, thermal reorganization of the traditional fishing grounds, and eastward redistribution. These findings demonstrate the value of nighttime fishing radiance for detecting environmentally structured fishery redistribution and suggest that early‐season KES‐related hydrographic variability is an important oceanographic context for the recent eastward shift of saury fishing grounds.